Mediating Effect of Sustainable Manufacturing Practices between Green Innovation Capability and Sustainability Performance among Malaysian Manufacturing SMEs - Lim, Wei Qi; Nadarajah, Devika; Wahab, Sazali Abd (Business Management and Strategy, 2022)
The level of innovative activities in Malaysia is still low compared to that of other nations, which is attributed to the scarcity of green innovation capability (GIC) and the minimal acquisition of new technological knowledge. Studies revealed that Malaysian manufacturing small and medium enterprises (SMEs) encounter the challenges of operation and supply chain disruption and tight cash flows. These firms would not want to venture into green equipment and eco technologies if there is no certainty of promising returns. Overall, studies on sustainable management systems in the Malaysian manufacturing SMEs have revealed that firms are still in the early stages of implementation, such that sustainable manufacturing practices (SMPs) are predominantly production- and process-oriented, neglecting the importance of the product life cycle and sustainable end-of-life management. The aim of this paper is: (1) To examine the effect of GIC on firm sustainability performance (SP) and (2) To investigate the mediating effect of SMPs on relationship between GIC and firm SP. Smart PLS 3.0 was applied to analyze the data collected among 150 ISO 14001 certified local SMEs manufacturers. The study demonstrated the non-significant result between GIC and SP; while SMPs mediated the relationship between GIC and SP. This study enriches the Dynamic Capability View (DCV) by extending the sustainability model to better explain the sustainable development process in the context of Malaysian manufacturing SMEs. This article does not just inform firms on the importance of SMPs for performance but also guides firm managers towards understanding and improving their current SMPs. These results also help Malaysian policy makers in providing appropriate assistance to improve current firm operations, and subsequently, sustainability-related outcomes. Following this, various kinds of assistance (e.g., strategic planning, governance, facility, financing, and technology) can be provided to support SMEs manufacturers.